A rare case of a blunt thoracic aortic injury in a patient with an aberrant right subclavian artery: A case report and literature review. (February 2021) - Diaz, Brandon; Meneses, Evander; Kinslow, Kyle; McKenney, Mark; Elkbuli, Adel; Boneva, Dessy
Highlights: Blunt thoracic aortic injuries are life threatening and require urgent intervention. Rare presentation of a blunt thoracic aortic injury in a patient with an aberrant right subclavian artery off the aortic arch distal to the takeoff of the left subclavian artery. An aberrant right subclavian artery originating from the aortic arch, distal to the left subclavian artery is an anatomic variant that adds significant complexity to TEVAR. Abstract: Introduction: Blunt thoracic aortic injuries (BTAIs) are an uncommon traumatic injury that if not treated promptly, can result in death. We present the case of a BTAI with aberrant aortic anatomy. Presentation of case: A 60-year-old female was involved in a motor vehicle crash where she suffered significant polytrauma including a BTAI. She was also found to have an aberrant right subclavian artery originating from the aortic arch. Thoracic Endovascular Aortic Repair (TEVAR) with a right common carotid artery to right subclavian artery bypass was accomplished. She required three more vascular surgical interventions, two for persistent type II endoleak and the third for left upper extremity acute limb ischemia. She had a 2-month hospital course for her devastating injuries and was eventually discharged home. A follow-up CT angiogram showed a stable thoracic aortic arch stent. Discussion: BTAIs are uncommon in the trauma population. In our patient who had an aberrant right subclavian artery, further procedures were required in the form of a right common carotid artery to right subclavian artery bypass and embolizations to resolve endoleaks. Conclusion: Blunt thoracic aortic injuries are life threatening and require urgent intervention. TEVAR is associated with better outcomes. An aberrant right subclavian artery originating from the aortic arch, distal to the left subclavian artery is an anatomic variant that adds significant complexity to TEVAR. TEVAR is still an option for repair of blunt thoracic aortic injuries despite anatomic variations as open repair still carries an increased risk of morbidity and mortality.